Estimativa do tempo de vida útil de represa de pequeno porte - Bufon, André Gustavo Mazzini; Landim, Paulo Milton Barbosa [UNESP]; De Melo, José Sávio Colares (Universidade Estadual de Maringa, 2009)
The purpose of this work is to compare two methods for time estimation of useful life for a small and shallow reservoir, located in Pirassununga, São Paulo State, Brazil: 1) sedimentometry; and 2) bathymetry. The model indicated a useful lifetime around 50 years for the studied dam. The values are between 51 years for the initial years of 1998/1999, and 46 years for the final years of 2004/2005, with an oscillation between 1999/2000 of 27 years, and between 2000/2001 of 76 years. The results show that it is possible to estimate the useful lifetime for small dams through the sedimentometric method, by knowing the correction coefficient value (K'). The coefficient is calculated using time values of useful lifetime calculated by the sedimentometric and bathymetric methods simultaneously, during the span of one year.
Estimate of useful lifetime for a small reservoir
Keywords: Bathymetry; Reservoir; Sedimentometry; Useful life